Commercial hand drawn batik apparel and its market potential with young Malaysians / Pegah Jahangiri - Pegah , Jahangiri (2017)
The purpose of this study was to seek a better understanding toward commercial hand-drawn batik apparel design and dress practice in the Klang Valley. This thesis looks into hand-drawn batik apparel from four perspectives. First it explores into contemporary hand-drawn batik developments, design and technique and related issues. Second it analyzes the youth perceptions and ideas toward hand-drawn batik specifications, design and influences of fashion and media. Third, it evaluates clothing values of the research sample and its relation with wearing hand-drawn batik apparel. At last it investigates the dress practice of youth in a batik context. This thesis is emphasizing on the ideas of youth about hand-drawn batik as a fashion wear and what influences them to wear batik or not. Lots of efforts have been put in bring batik back to mode; but how often do we see people especially youngsters wear hand-drawn batik apparel? An introductory pilot study was done by researcher to support the significance of this research and showed that the total of 84% agreed that younger generations prefer to wear other garments rather than batik. So, it is necessary to define the reasons that influence the popularity of hand-drawn batik as a dress practice in young generation. This study used mixed methods research which combines quantitative and qualitative approaches. Qualitative phase is an exploratory research and the instrument used in this part was semi-structured interviews with open-ended questions, sampling method was non-probability sampling purposive sampling plus saturation and respondents were expert individuals in the area of batik. Quantitative phase used explanatory survey design method which describes and define trends in the population; dependent variable (DV) in this study is the selection and use of hand-drawn batik clothing which is influenced by independent variables that include hand-drawn batik specifications, aesthetic in design, fashion influences, media influences and clothing values. The instrument used was a Likert scale questionnaire in this phase. The questionnaire validity was fully investigated and accepted by consulting with research experts (n=5) and among internal consistency methods the Cronbach's coefficient alpha was chosen to check the reliability of the instrument and the reliability test result was (α = 0.913). Research sample were young individuals aged 19 to 25 from undergraduate students from University of Malaya; both genders, ethnic groups and racial composition were included. The sample size was (n=375) defined by Morgan table for determining sample size from a given population. Statistical Package for the Social Sciences (SPSS) is used in this phase of the research. The findings provided the factors and reasons which shaped the process of development, influenced the popularity of batik dress practice in youngsters and defining the related issues of hand-drawn batik in fashion designing; it is hoped that the outcomes of this study can improve hand-drawn batik apparel in order to satisfy the taste and need of young fashion consumers of today.